CORRELATION ANALYSIS BETWEEN METRIC PARAMETERS OF PARENCHYMATOUS COMPONENTS OF RAT SUBMANDIBULAR GLANDS UNDER THE EFFECT OF ETHANOL - Shevchenko, K.V.; Yeroshenko G.А.; Solod, A.V.; Lysachenko, O.D.; Yakushko, O.S.; Boruta, N.V.; Lichman, D.V.; Kramarenko, D.R. (World of Medicine and Biology, 2020)
The effect of ethanol on the salivary glands is manifested by changes in morphometric parameters of both the final departments and excretory ducts. But taking into account that the obtained large number of morphometric indicators is rather complicated, then there is a need for a correlation analysis, where the presence of dependencies between morphometric indicators was determined using the Bravais – Pearson coefficient. It was established that diagnostic criteria for assessing the functional state of rat submandibular glands after ethanol is manifested by the dependence of the outer diameter, lumen diameter and epithelial cell height on day 12 in all parenchymal components, which corresponds to the formation of chronic alcohol dependence in rats.